Is advice incompatible with autonomous informed choice? Women's perceptions of advice in the context of antenatal screening: a qualitative study. (19th April 2012) - Ahmed, Shenaz; Bryant, Louise D.; Tizro, Zahra; Shickle, Darren
Abstract Background Patient autonomy in antenatal screening is a high priority for policy developers in many countries. Objective This paper presents women's understandings of how health professionals should facilitate informed screening choices with an emphasis on their understandings of autonomy and advice. Design, setting and participants The study was carried out in 2009 in the UK, using a qualitative approach. Ninety‐eight participants of African, British White, Caribbean, Chinese and Pakistani origin had semi‐structured interviews, which were analysed using framework analysis. Results Four themes were identified during the analysis: 'Meanings of advice in antenatal screening: the advice continuum', 'Recognition of the role of health professionals in decision making', 'Understandings of advice in the context of autonomous decision making' and 'Reasons given for wanting advice'. Women said they valued advice from health professionals to make decisions about antenatal screening, but their understandings of 'advice' ranged from information giving only to direction about screening choices. Conclusion Many women wanted health professionals to support the process of making informed choices by engaging in discussion and did not see advice as incompatible with making autonomous choices. However, some women wanted direction about whether to have a screening test or not, something which policy and guidelines explicitly prohibit. This may cause an ethical dilemma for health professionals who are required to both support women's preference for care and adhere to a policy of non‐directiveness. Further clarification is needed on how health professionals should support the process of making informed choices when women ask for clear direction on screening choices.